Effect of Early Childhood Malnutrition on Tooth Eruption Sequence in Nepalese Children - Shrestha, Nameeta; Acharya, J. (Tribhuvan University Journal, 2020)
Child under-nutrition has effects which last a lifetime. The consequences can be both short term and long term. Malnourished children tend to be physically, emotionally and intellectually less productive and suffer more from chronic illnesses and disabilities compared to healthy children. The objective of this study was to determine prevalence of under-nutrition and investigate association between early childhood malnutrition and deciduous tooth eruption in children aged 0-59 months in Mugu district of Nepal. A structured questionnaire based on Nepal Demographic and Health Survey 2011 questionnaire was used. Weight and height of 246 children, aged 0-59 months were measured. Dental caries status and eruption sequence were noted. Among the total, 14 .1% had moderate/severe wasting of muscles, 25.2% were moderately stunted and 36.6% were severely stunted. From the total, 30 .5% were moderately underweight and 18.3% were severely underweight. A significantly higher proportion with wasting presented with delayed eruption sequence than those without wasting (p